Empowering communities through solar energy: A strategic response to power deficits - Hamdani Hamdani; Dwiprima Elvanny Myori; Ali Basrah Pulungan; Adam Rasyid Sidiqi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Mushalla Longga Congkeh in Guguak District, Lima Puluh Kota Regency frequently experiences electricity shortages that disrupt worship and daily community activities. This community service program aims to address the limited electricity supply through the implementation of Appropriate Technology (TTG) in the form of a Solar Power Generation System (PLTS). The implementation methods include socialization, technical training, and mentoring of the local community during the installation and maintenance of the PLTS system. The main objective is to improve access to renewable, environmentally friendly, and sustainable energy sources. The program successfully installed a 100 Wp PLTS system capable of producing approximately 400 WH of electricity per day, sufficient to meet the lighting and sound system needs of the mushalla. The impact of this activity is measured quantitatively through increased electricity availability, reduced operational costs, and improved community energy independence. This program demonstrates that solar energy utilization offers a concrete solution to electricity shortages, and its implementation model has the potential to be replicated in other regions facing similar energy access challenges.